Characteristics of Romania’s External Trade in Agri-Food Products with Bulgaria - Tudorel ANDREI (Communications of International Proceedings, 2021)
The study aims to identify characteristics related to Romania’s exports and imports of agri-food products and resulting from the trade with Bulgaria over the last thirty years. This research uses statistical data on trade at the level of the twenty-four categories of products that are covered by the external trade classification. By employing the multiple regression model, a dependence between the degree of concentration of exports of agri-food products and that of imports of such products per product category is identified. The statistical data used show us that the accession of the two countries to the European Union led to an increase in the volume of external trade but also to a diversification of the Romanian imports from Bulgaria.
Keywords: External Trade; Theil Index; Regression Model.